Perfil del profesional y su incidencia en la gestión secretarial en el departamento de Secretaría General del Gobierno Autónomo Descentralizado Municipal Quinsaloma - Duarte Montiel, Karen Lizeth (2020)
The following research work has been carried out with the purpose of establishing how the professional profile affects secretarial efforts in the Department of General Secretary of the Autonomous Decentralized Municipal Government Quinsaloma. The professional profile is currently a great help to occupy the positions that are needed who require them, which is why for years they have worked in professional training of the secretaries and so over the years they ceased to be the secretary that only serves the Coffee and attends to users to become the assistant or executive secretary, that is, the person who knows everything that happens around their work area and the company, that is why this research has been able to develop what are the steps that the secretaries perform, the attention they should provide, such as organizing the life of the immediate boss, whether personal or work. Therefore, we worked with a theoretical framework in which the reality of the two study variables could be described, in the same way the survey technique was applied both to the secretaries of the Municipal Quinsaloma GAD and to the citizens of this canton and This results in the problem existing in the public entity because the relevant secretarial procedures are not carried out in order to improve its efficiency and effectiveness of its work in the office. The idea lies in the proposal to present an instruction manual for secretarial procedures so that the secretaries of this public entity have a guide on how the correct way to perform their functions within the company will be.